A multi-criteria decision model based on the evidential reasoning approach for the selection of fulcrum ports supporting Arctic shipping through the Northeast Passage. Issue 2 (17th February 2022) - Yao, Shuaiyu; Hu, Hao; Chen, Yu-Wang; Ouyang, Wendi
ABSTRACT: As a result of the opening Arctic waters, Arctic Northeast Passage (NEP) can be used as a shortcut between Asian and European ports, which may bring considerable economic benefits. Due to the harsh environment and substantial costs, it is difficult to construct many fulcrum ports along the Russian Arctic coast, which provide support services for ships navigating the NEP. A multi-criteria decision model is hence constructed to select fulcrum ports among candidates to support Arctic shipping through the NEP. Based on the model, the evidential reasoning (ER) approach is used to aggregate quantitative data and qualitative expert judgments to generate distributed assessments for candidate ports, as well as modeling uncertainties such as incompleteness and ignorance in the assessment of candidate ports. Their suitability as fulcrum ports are prioritized according to the utilities. The results show that Pevek, Sabetta, and Murmansk are the ideal fulcrum ports for the eastern, central, and western section, respectively, of the Russian Arctic coast. The associated policy recommendations include prioritizing the improvement of selected fulcrum ports, attaching importance to promising candidate ports, updating outdated infrastructure, and implementing more related projects. A sensitivity analysis conducted in this study validates the feasibility and reasonability of the proposed model.